Desarrollo de la creatividad y su impacto en los métodos de aprendizaje en los estudiantes de quinto año de la escuela de educación básica Juan E. Verdesoto, del cantón Babahoyo de la Provincia de Los Ríos - Valero Pisco, Johanna María (2021)
Cultivating students' creativity helps them reflect, criticize, and innovate; Today, students must be competitive to play a role in today's society and world. Creative thinking helps develop cognitive skills and abilities, such as abstract thinking found in everyday life, understanding, communication, reasoning, learning, planning, and problem-solving skills. The development of creative thinking allows practice and problem analysis to be solved in the right way. When students begin to perform mental exercises such as comparison, classification and reflection, they are very successful in the field of education. Another factor is study habits and planning time for each topic, which helps to be responsible and increasingly creative. The development of creative thinking has formed human beings with the capacity for reflection, capable of living in an increasingly competitive world in which daily problems arise and must seek the best alternative solutions. Teachers have the inescapable responsibility to train schoolchildren in this way, so that they can develop their capacities to the maximum and have real and lasting rational thinking. Creativity will give quality thinking, the ability to develop your thoughts in an appropriate and clear way, and we will be able to find faults and separate illogical arguments. The journey through the concept of creativity and its components offers the possibility of revealing the disconcerting vision of this dimension of people, which arises as a skill that can be developed in each person and thus can be an education. Finally, by allowing students to engage in creative learning activities in the classroom, some teaching methods and teaching guidelines related to teaching suggestions to enhance creative ability are proposed.